Observational clinical study of a new emollient in 26 patients with atopic dermatitis. - Rigoni, C.; Cantù, A.M.; Gelmetti, C. (European Journal of Pediatric Dermatology, 2018)
According to the Authors, the barrier defect plays an important role not only in dermatitis but also in other atopic conditions. While not ignoring the role of defect in immune regulation, in the latest systematic review the role of emollients is re-evaluated especially in the prevention of exacerbations of atopic dermatitis. Not all the emollients are the same and the most interesting are those that, thanks to the use of natural anti-inflammatory substances and prebiotics, seem to be able to decrease the itching and make the life of Staphylococcus aureus more difficult. In particular, the efficacy and tolerability of RILASTIL XEROLACT ATOPIC balm1 and bath oil2 were studied leading the Authors to conclude that they can represent a useful tool in the armament of the physician that must cure atopic dermatitis.